Kerukunan antar Umat Beragama Di Desa Banaran(Studi Hubungan Antar Umat Islam, Kristen Protestan, Katolik, Hindu Dan Buddha) - , Sriyono; , Drs. M. Darojat Ariyanto, M.Ag (2017)
In the village of Banaran, Grogol subdistrict, Sukoharjo regency there are followers of Islam, Protestantism, Catholicism, Hinduism and Buddhism. In the midst of social plurality in the different religious beliefs was able to build a sense of mutual respect among religions. thats social conditions makes author's interested in conducting research on inter-religious harmony in the Banaran village (The Study of Relationships between Muslims, Protestant, Catholic, Hindu and Buddhist). The author conducted research with the aim to find out the views of religious leaders and harmony management among people in the banaran village. The research method is to determine what type of research is a qualitative field. Took placa in Banaran village, Grogol, Sukoharjo. The research subjects or informants are people who give direct information about the situation and condition of research background. In this case the informant is the people in Banaran village especially religious leaders and the Banaran village government. Data analysis methods, first, the author will read, study, and examine the data authors got from interviews and observations collected as well as other data. second, the overall data reduction of the data that has been read, studied, and analyzed in order to be categorized according to each type of data. After this process, the authors put forward in the form of a report or the results obtained from the outcome of these studies in descriptive analysis, which was the presentation in the form of writing that explains what is in accordance with those obtained from research. The Results of the study are point of views of Banaran village religious leaders about the importance of inter-religious harmony, where the plurality in society motivated by religious differences are very susceptible to friction. The friction could be caused by their view of the small fraction of people who are less open minded in interaction with the community. Thus the religious leaders who coordinate to conduct training in their respective followers to always maintain inter-religious harmony. Management of inter-religious harmony by religious leaders is to conduct active communication with fellow religious leaders through formal meeting has been scheduled, and non-formal and informal meetings while interacting in a certain time situationaly in order to maintain harmony condition that has lasted. Keyword: Inter-Religious Harmony, in Banaran Village, The Study of Relationships between Muslims, Protestant, Catholic, Hindu and Buddhist.